THE ANALYSIS OF LIQUEFACTION PHENOMENON OF THE FLEXIBLE PAVEMENT USING SEISMIC MONITORING EQUIPMENT - KUSUMAWARDANI, RINI; Nugroho, Untoro; Handayani, Sri; Fananda, Mareta Aspirilia (IIUM Engineering Journal, 2019)
ABSTRACT: Liquefaction phenomenon is generally caused by high dynamic vibrations in a very fast duration. This article investigated the behavior of dynamic vibrations caused by vehicles on the road. This study employed the HVSR (Horizontal Vertical Spectral Ratio) with an accelerometer. The result of dynamic vibration generated by the passing vehicle or the micro tremor / micro seismic vibration was recorded by seismic monitoring devices. This seismic monitoring equipment converted vibration into natural frequency (f0) and amplification (A0) using Geopsy software. The result of HVSR (Horizontal Vertical Spectral Ratio) was the soil vulnerability index (Kg). The results of this study indicated that the three parameters above were then analyzed with the assumption that if the amplification value (A0) was higher and associated with a lower natural frequency value (Æ’0) with a high vulnerability index (Kg), then the area had the potential liquefaction, with laboratory research results in the form of granular gradation testing as the supporting data. Therefore, the results of the analysis and the laboratory can concluded that the three research locations have the potential liquefaction. ABSTRAK: Fenomena pececairan umumnya disebabkan oleh adanya getaran dinamik tinggi dalam tempoh yang sangat cepat. Artikel ini mengkaji fenomena getaran dinamik yang disebabkan oleh kenderaan di jalan raya. Kajian ini menggunakan HVSR (Nisbah Spektral Menegak Mendatar) dengan pecutan. Hasil getaran dinamik yang dihasilkan oleh kenderaan yang melalui atau gegaran mikro / mikro getaran seismik dicatatkan oleh alat pemantauan seismik. Peralatan pemantauan seismik ini mengubah getaran ke frekuensi semula jadi (f0) dan amplifikasi (A0) menggunakan perisian Geopsy. Hasil HVSR (Nisbah Spektral Vertikal Mendatar) adalah indeks kelemahan tanah (Kg). Keputusan kajian ini menunjukkan bahawa ketiga-tiga parameter di atas kemudian dianalisis dengan anggapan bahawa jika nilai amplifikasi (A0) lebih tinggi dan dikaitkan dengan nilai kekerapan semulajadi yang lebih rendah (Æ’0) dengan indeks kelemahan tinggi (Kg), maka kawasan mempunyai potensi pencairan, dengan hasil penyelidikan makmal berupa pengujian gradasi granular sebagai data pendukung. Oleh itu, hasil analisis dan makmal dapat menyimpulkan bahawa tiga lokasi penyelidikan mempunyai potensi adanya pececairan.